THE URGENCE OF RENEWING COMPANY REGULATIONS ACCORDING TO LAW NUMBER 11 OF 2020 AT PT. BAHTERA BAHARI SHIPYARD - Martalina Martalina; Nur Hadiyati (ConCEPt - Conference on Community Engagement Project, 2022)
This paper aims to provide further explanation regarding the urgence of renewing Company Regulations according to Law Number 11 of 2020 concerning Job Creation. Due to the Covid-19 pandemic, all sectors were affected and many struggle to survive. Considering that in Indonesia there have been many regulations that have been made, therefore, there is often overlap between regulations which then creates a conflict of authority between one institution and another. These factors then strengthen the reasons for the ratification of Law Number 11 of 2020 concerning Job Creation which also known as Omnibus Law, even when it has received a lot of criticism from various parties. Every company engaged in the trade of services and/or goods, in the realization of its management and daily activities related to employment, definitely requires a company regulation in accordance with applicable regulations and is obeyed by all employees in order for the company to run well. Based on the principle of lex posterior derograt legi priori, where the interpretation of the new law overrides the old law. In this case, the current labor regulation is Law Number 11 of 2020 concerning Job Creation, while the old law is Law Number 13 of 2003 concerning Manpower. In carrying out Community Engagement Project, the author conducts interviews with partner’s representatives and observes partner’s location. The output target of this activity is to assist partners in the preparation of legal document. The revised Company Regulation is then submitted to partners. Furthermore, the author provides an explanation of the contents of the clauses from the output of the activity, so that there are no misunderstandings or misunderstandings from the partners. And then the output of this activity will be directly implemented and used as a guide for partners in running their business.